2022
DOI: 10.1002/smll.202106640
|View full text |Cite
|
Sign up to set email alerts
|

In‐Situ Synthesis of Carbon‐Encapsulated Atomic Cobalt as Highly Efficient Polysulfide Electrocatalysts for Highly Stable Lithium–Sulfur Batteries

Abstract: Lithium–sulfur (Li–S) batteries have been considered as one of the most promising electrochemical energy storage systems because of their high energy density. However, a series of issues severely limit the practical performances of Li–S batteries such as low conductivity, significant volume change, and shuttle effect. The hollow carbon spheres with huge voids and high electrical conductivity are promising as sulfur hosts. Unfortunately, the nonpolar nature of carbon materials cannot prevent the shuttle effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 58 publications
0
31
0
Order By: Relevance
“…To further analyze the chemical structure, NMR spectroscopy of the self-standing CTP nanofilm was performed (Figure 3f). And the 13 C NMR spectrum indicates two explicit chemical shift peaks at 163.8 and 43.7 ppm, which correspond to the C of triazine and piperazine, respectively. [39] It affirms that the CTP nanofilm consists of two components.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To further analyze the chemical structure, NMR spectroscopy of the self-standing CTP nanofilm was performed (Figure 3f). And the 13 C NMR spectrum indicates two explicit chemical shift peaks at 163.8 and 43.7 ppm, which correspond to the C of triazine and piperazine, respectively. [39] It affirms that the CTP nanofilm consists of two components.…”
Section: Resultsmentioning
confidence: 99%
“…The X-ray photoelectron spectroscopy was conducted by XPS (ThermoFisher, ESCALAB250Xi). 13 C NMR spectrum of self-standing CTP nanofilm was used to analyze the chemical structure by Bruker 400M.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately three-quarters of the capacity of LSBs is provided by the conversion from long-chain LiPSs to insoluble Li 2 S 2 /Li 2 S, and the poor reaction kinetics of this process leads to the accumulation of LiPSs on the cathode side, shuttling to the anode side under the influence of the concentration gradient on both sides of the cathode–anode electrode. Furthermore, the accumulation of LiPSs leads to the random precipitation and agglomeration of Li 2 S into large particles with high activation energy, making it difficult to be reused in the subsequent reaction. , Therefore, the problem of sluggish redox kinetics of LiPSs/sulfides blocked on the cathode side still needs to be solved, and a more efficient method is urgently needed, which not only anchors LiPSs but also accelerates the subsequent catalytic conversion of LiPSs to improve the long-term cycling stability of LSBs. , Nowadays, the exploration of electrocatalysts for the catalytic conversion of LiPSs has attracted extensive attention from researchers focusing on LSBs. …”
Section: Introductionmentioning
confidence: 99%
“…33,34 Therefore, the problem of sluggish redox kinetics of LiPSs/sulfides blocked on the cathode side still needs to be solved, and a more efficient method is urgently needed, which not only anchors LiPSs but also accelerates the subsequent catalytic conversion of LiPSs to improve the long-term cycling stability of LSBs. 35,36 the exploration of electrocatalysts for the catalytic conversion of LiPSs has attracted extensive attention from researchers focusing on LSBs. 37−42 Researchers have demonstrated that single-atom catalyst and transition-metal compounds exert catalytic effects on LiPSs, not only effectively inhibiting their shuttling through chemical binding but also significantly accelerating their redox reaction.…”
Section: ■ Introductionmentioning
confidence: 99%